Prone Position during ECMO is Safe and Improves Oxygenation. Issue 11 (November 2013) - Kipping, Valesca; Weber-Carstens, Steffen; Lojewski, Christian; Feldmann, Paul; Rydlewski, Antje; Boemke, Willehad; Spies, Claudia; Kastrup, Marc; Kaisers, Udo X.; Wernecke, Klaus-D.; Deja, Maria
Purpose: Combination of prone positioning (PrP) and extracorporeal membrane oxygenation (ECMO) might be beneficial in severe acute respiratory distress syndrome (ARDS), because both approaches are recommended. However, PrP during ECMO might be associated with complications such as dislocation of ECMO cannulae. We investigated complications and change of oxygenation effects of PrP during ECMO to identify "responders" and discuss our results considering different definitions of response in the literature. Methods: Retrospective analysis of complications, gas exchange, and invasiveness of mechanical ventilation during first and second PrP on ECMO at specified time points (before, during, and after PrP). We used multivariate nonparametric analysis of longitudinal data (MANOVA) to compare changes of mechanical ventilation and hemodynamics associated with the first and second procedures. Results: In 12 ECMO patients, 74 PrPs were performed (median ECMO duration: 10 days (IQR: 6.315.5 days)). No dislocations of intravascular catheters/cannulae, endotracheal tubes or chest tubes were observed. Two PrPs had to be interrupted (endotracheal tube obstruction, acute pulmonary embolism). PaO2 /FiO2 -ratio increased associated with the first and second PrP (p = 0.002) and lasted after PrP in 58% of these turning procedures ("responders") without changes in ECMO blood flow, respiratory pressures, minute ventilation, portion of spontaneously triggered breathing, and compliance. Hemodynamics did not change with exception of increased mean pulmonary arterial pressure during PrP and decrease after PrP p≤0.001), while norepinephrine dosage decreased (p = 0.03) (MANOVA). Conclusions: Prone position during ECMO is safe and improves oxygenation even after repositioning. This might ameliorate hypoxemia and reduce the harm from mechanical ventilation.